Run for the team: An analysis of effort gains in track and field relays - Schleu, J. E.; Mojzisch, A.; Hüffmeier, J. (Psychology of Sport and Exercise, 2019)
Objectives: We studied whether effort gains in relay as compared to individual swimming competitions generalize to 4 × 400 m track and field relays. Design: We employed a 4 (indispensability levels) × 2 (relation of team performance and team outcomes) design. Method: German national squad runners (N = 23) were surveyed on their effort expenditure. In our main study, we tested within-person performance differences (N = 397) between individual and relay competitions relying on archival data from major track and field championships. We operationalized the indispensability of one`s own contribution via relay positions and the relation of team performance and outcomes via medal chance. Results: Athletes reported effort gains in relay as compared to individual competitions. The archival study revealed effort gains for later positions if the relay had a high medal chance. These effort gains showed an unexpected quadratic pattern across the relay with smaller effort gains at the last position.